Serotype, antibiotic susceptibility and whole-genome characterization of Streptococcus pneumoniae in all age groups living in Southwest China during 2018–2022 - Miao, Chenglin; Yan, Ziyi; Chen, Chunmei; Kuang, Linghan; Ao, Keping; Li, Yingying; Li, Jialu; Huang, Xiaocui; Zhu, Xinghua; Zhao, Yijia; Cui, Yali; Jiang, Yongmei; et al. (Frontiers in Microbiology, 2024)
Background Streptococcus pneumoniae is a common pathogen that colonizes the human upper respiratory tract, causing high morbidity and mortality worldwide. This study aimed to investigate the prevalence status of S. pneumoniae isolated from patients of all ages in Southwest China, including serotype, antibiotic susceptibility and other molecular characteristics, to provide a basis for clinical antibiotic usage and vaccine development. Methods This study was conducted from January 2018 to March 2022 at West China Hospital, West China Second University Hospital, First People’s Hospital of Longquanyi District (West China Longquan Hospital), Meishan Women and Children’s Hospital (Alliance Hospital of West China Second University Hospital) and Chengdu Jinjiang Hospital for Women and Children Health. Demographic and clinical characteristics of 263 pneumococcal disease (PD) all-age patients were collected and analyzed. The serotypes, sequence types (STs), and antibiotic resistance of the strains were determined by next-generation sequencing, sequence analysis and the microdilution broth method. Results The most common pneumococcal serotypes were 19F (17.87%), 19A (11.41%), 3 (8.75%), 23F (6.46%) and 6A (5.70%). Coverage rates for PCV10, PCV13, PCV15, PCV20 and PCV24 were 36.12, 61.98, 61.98, 63.12 and 64.26%, respectively. Prevalent STs were ST271 (12.55%), ST320 (11.79%), ST90 (4.18%), ST876 (4.18%) and ST11972 (3.42%). Penicillin-resistant S. pneumoniae (PRSP) accounted for 82.35 and 1.22% of meningitis and nonmeningitis PD cases, respectively. Resistance genes msrD (32.7%), mefA (32.7%), ermB (95.8%), tetM (97.3%) and catTC (7.6%) were found among 263 isolates. Most isolates showed high resistance to erythromycin (96.96%) and tetracycline (79.85%), with more than half being resistant to SXT (58.94%). A few isolates were resistant to AMX (9.89%), CTX (11.03%), MEN (9.13%), OFX (1.14%), LVX (1.14%) and MXF (0.38%). All isolates were susceptible to vancomycin and linezolid. Conclusion Our study provides reliable information, including the prevalence, molecular characterization and antimicrobial resistance of S. pneumoniae isolates causing pneumococcal diseases in Southwest China. The findings contribute to informed and clinical policy decisions for prevention and treatment.